Adsorption of Sulphur Dioxide Using Natural and Modified Gördes Clinoptilolites - Burcu Erdoğan Alver; Meryem Sakizci; Ertuğrul Yörükoğullari (Adsorption Science & Technology)
The adsorption of SO 2 onto clinoptilolite-rich zeolite tuff from Gördes (Turkey) (natural-G) and its cation-exchanged (Na + , K + , Ca 2+ and Mg 2+ ) forms was investigated up to 100 kPa pressure at two different temperatures (273 K and 293 K). The structural properties of the clinoptilolites were studied by X-ray diffraction (XRD) and Fourier-transform infrared (FT-IR) spectroscopy. Quantitative XRD analysis showed that the major component of the natural-G sample was clinoptilolite, together with minor amounts of feldspar, opal-CT, smectite, mica-illite and amorphous material (opal-A). It was established that the uptake of SO 2 onto the adsorbents increased in the order Ca-G < natural-G < Mg-G < K-G < Na-G at both temperatures.